2018
DOI: 10.1017/ice.2018.150
|View full text |Cite
|
Sign up to set email alerts
|

Active screening and interfacility communication of carbapenem-resistant Enterobacteriaceae (CRE) in a tertiary-care hospital

Abstract: Active screening for CRE is feasible, and screening patients transferred from outside facilities to the medical or surgical ICU resulted in the highest screen positivity rate. Furthermore, CRE carriage was inconsistently documented in transfer paperwork, suggesting that admission screening or enhanced inter-facility communication are needed to improve the identification of CRE-colonized patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 23 publications
0
18
0
1
Order By: Relevance
“…This estimate is higher than the proportion of CRE (3.1%) among clinical isolates reported to the National Healthcare Safety Network in 2015 24 and considerably higher than the 0.5% CRE admission prevalence recently reported at a Chicago tertiary-care hospital (2013 data from ICU populations). 16 Importantly, most colonized patients (54%) were not on contact precautions at unit admission (for any indication), posing a potential reservoir for transmission during their unit encounter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This estimate is higher than the proportion of CRE (3.1%) among clinical isolates reported to the National Healthcare Safety Network in 2015 24 and considerably higher than the 0.5% CRE admission prevalence recently reported at a Chicago tertiary-care hospital (2013 data from ICU populations). 16 Importantly, most colonized patients (54%) were not on contact precautions at unit admission (for any indication), posing a potential reservoir for transmission during their unit encounter.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent CRE data indicate that existing targeted screening policies (eg, for recent foreign hospitalization, on direct transfer from outside facilities) miss many colonized patients. 16,17 Better identifying predictors of colonization and developing algorithms to predict colonization probability may improve targeted screening approaches. Existing strategies often rely on risk factors (ie, "independent" variables), but strong risk factors may not be good predictors.…”
mentioning
confidence: 99%
“…8 Unfortunately, our survey revealed that positive CRE/CP-CRE status is communicated less than half the time to the patient, a finding previously demonstrated in other studies including those in non-VA settings. 9,10 The greater proportion of respondents reported transfer communication between VA facilities in our survey is encouraging and may be due to their common EHR. However, the implementation of standardized interfacility transfer notification and the development of regional CRE/CP-CRE registries are important steps toward improving communication.…”
Section: Discussionmentioning
confidence: 76%
“…In decreased the spread of multidrug-resistant organisms in inpatient health care settings (16,17). Additionally, antibiotic exposure has been associated with communityacquired ESBL-Ent in adults in Chicago (18).…”
Section: Discussionmentioning
confidence: 99%